Observation of a slanted moisture structure with weak updraft leading to localized heavy rainfalls - Satoru Yoshida; Tetsu Sakai; Tomohiro Nagai; Hiromu Seko; Teruyuki Kato; Koichi Shiraishi; Shingo Shimizu (Scientific Reports)
Abstract Understanding moisture structures within moist low-level jets (MLLJs) that fuel moisture into mesoscale convective systems (MCSs) is essential for revealing the development of MCSs that cause localized heavy rainfalls. The moisture structure in MLLJs and the mechanisms that determine it are unclear. We used radiosondes, a water vapor lidar, and Doppler lidar to observe MLLJs in Kyushu, western Japan. The observations revealed an unstable moist layer that was saturated or nearly saturated and that extended vertically from near the surface to more than 1 km above sea level in the MLLJ. The thickness of the moist layer gradually increased with a slant angle of less than 1° toward the MCS. The MLLJ involved weak updrafts below the cloud bases that contributed to thickening the slanted moist layer via vertical transport of moisture. The slanted moisture structure with a weak updraft appeared to effectively fuel moisture into MCSs and led to localized heavy rainfalls.